2002
DOI: 10.1016/s0022-5347(05)64915-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Ovariectomy and Simulated Birth Trauma on the Lower Urinary Tract of Female Rats

Abstract: Apoptosis in the urethra occurs 9 months after castration and simulated birth trauma. However, this finding was not seen in the muscle layers or in other urogenital tissues. Some ultrastructural changes also occurred that may explain some symptoms that women have after vaginal childbirth and menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 20 publications
4
39
0
4
Order By: Relevance
“…The measurement of threshold pressure (TP) was determined during cystometric examination as previously described (16,19). It is defined as the difference between the bladder pressure immediately before micturition and the baseline pressure at the beginning of the saline infusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of threshold pressure (TP) was determined during cystometric examination as previously described (16,19). It is defined as the difference between the bladder pressure immediately before micturition and the baseline pressure at the beginning of the saline infusion.…”
Section: Methodsmentioning
confidence: 99%
“…In the past few years, some useful rat animal models have been proposed such as simulating birth trauma with intravaginal balloon inflation (1,4,15), vaginal distension, and ovariectomy (12,19), pudendal nerve crush (4,7,10), spinal cord injury (21,28), and electrocauterization (2,27). These important investigations have shed light on the pathogenesis of SUI.…”
mentioning
confidence: 99%
“…Resplande et al used the same technique of vaginal distention in immediately postpartum rats using an 18Fr catheter inflated to 5 ml for 4 hours. 22 Cannon et al performed predilation of the vagina by inserting increasing sizes (24Fr to 32Fr) of urethral dilators to accommodate the vagina of virgin rats, followed by VD using 10Fr catheters inflated to 3 ml. 24…”
Section: Models Simulating Maternal Childbirth Injuriesmentioning
confidence: 99%
“…Pelvic adhesions, however, were not observed at dissection. Resplande et al (22) studied the vaginal walls of rats after distention injury and found marked vaginal mucosal atrophy, an increase in collagen content, and a decrease in the muscular layer. The vaginal specimens also were contracted, appearing with many folds in the subepithelial layer (22).…”
Section: Discussionmentioning
confidence: 99%
“…Resplande et al (22) studied the vaginal walls of rats after distention injury and found marked vaginal mucosal atrophy, an increase in collagen content, and a decrease in the muscular layer. The vaginal specimens also were contracted, appearing with many folds in the subepithelial layer (22). This increased collagen content between stromal cells of the vaginal wall perhaps protects the vagina from progression to its most severe degree of decensus.…”
Section: Discussionmentioning
confidence: 99%